Anti-inflammatory and Pro-apoptotic Effects of 18beta-Glycyrrhetinic Acid In Vitro and In Vivo Models of Rheumatoid Arthritis - Feng, Yunhui; Mei, Liyan; Wang, Maojie; Huang, Qingchun; Huang, Runyue (Frontiers in Pharmacology, 2021)
18beta-Glycyrrhetinic acid (18β-GA), an active component from Glycyrrhiza glabra L. root (licorice), has been demonstrated to be able to against inflammatory response and reduce methotrexate (MTX)-derived toxicity. This study was therefore designed to test the therapeutic possibility of 18β-GA on Rheumatoid arthritis (RA) and explore the underlying mechanism. LPS or TNF-α induced inflammation cell models and collagen-induced arthritis (CIA) animal model were applied in this study. Quantitative real-time PCR (qRT-PCR) and western blot were performed to analyze genes and proteins expression of inflammatory cytokines and signaling pathways. MTS and colony-forming assay were used to test the impact of 18β-GA on cell proliferative capacity. Cell apoptosis assay and cell cycle assay were carried out by using flow cytometry. Hematoxylin and eosin (H&E) staining was conducted to evaluate pathological changes. Enzyme-linked immunosorbent assay (ELISA) was performed to detect cytokines secretion. In vitro, we found that multiple pro-inflammation cytokines (IL-1β, IL-6, and COX-2) were decreased by 18β-GA through inhibiting MAPK/NF-κB signaling pathway. Moreover, 18β-GA was able to suppress cell viability, trigger cell apoptosis, and induce G1 phase cell cycle arrest in our in vitro studies. 18β-GA dramatically enhanced the level of FOXO3 in both TNF-α- and LPS-induced inflammation in vitro models. Interestingly, FOXO3 gene was identified significantly decreased in RA synovial tissue as compared to healthy control in multiple microarray studies from the GEO dataset. In vivo, 18β-GA exhibited a promising therapeutic effect in a collagen-induced arthritis mouse model by alleviated joint pathological changes and declined serum levels of TNF-α, IL-1β, and IL-6. Finally, we observed that 18β-GA administration can mitigate liver damage caused by collagen or MTX. Collectively, the current study for the first time demonstrated that 18β-GA can inhibit inflammation and proliferation of synovial cells, and the underline mechanism might be associate with its inhibition of MAPK/NF-κB signaling and promotion of FOXO3 signaling. Therefore, 18β-GA is expected to be a new drug candidate for RA therapy.